A smooth variable structure control algorithm for robot manipulators - Machado, J. A. Tenreiro (1988)
A new sliding controller is proposed. Second order linear system sliding curves eliminate the reaching phase and consequently and associated problems of load sensitivity and high demanded torque. Moreover, the chattering usually present in the sliding phase also disappears with the new control law. Simulation results show a negligible coupling between axes, thus enabling an easier and more efficient controller adjustment. It is also shown that the controller parameter set can be easily adjusted, and there is a large set of possible quasi-optimal values. This is of utmost importance, when one thinks of the industrial applications of this type of algorithms. Experiments were developed based on the position control problem. Nevertheless, generalization to the trajectory tracking problem is trivial. In either case the controller computational requirements are low, thus well adapted to today's microprocessor based digital control technology.